New species and new records of Manota Williston (Diptera: Mycetophilidae) in the Neotropical region - Hippa, Heikki (Zootaxa, 2013)
The following 17 new species are described: Manota anfracta (Ecuador), M. appendiculata (Ecuador, French Guyana), M. aristata (Ecuador), M. bisulca (Ecuador), M. depilis (Ecuador), M. inermis (Ecuador), M. iota (Ecuador, French Guy-ana), M. micula (Ecuador), M. panda (Argentina), M. papillosa (Ecuador), M. patula (French Guyana), M. paula (Ecua-dor), M. pisinna (French Guyana), M. quantilla (Ecuador), M. quantula (Ecuador), M. senta (Nicaragua), M. virgata (Ecuador). New records of the following species are given: Manota acuminata Jaschhof and Hippa (Ecuador), M. acuti-stylus Jaschhof and Hippa (Ecuador, French Guyana), M. diversiseta Jaschhof and Hippa (Ecuador, French Guyana), M. ibanezi Hippa and Huerta (Ecuador, French Guyana, Peru), M. inornata Jaschhof & Hippa (French Guyana), M. multise-tosa Jaschhof and Hippa (Ecuador), M. parva Jaschhof and Hippa (Ecuador), M. rotundistylus Jaschhof and Hippa (Ecua-dor), and M. squamulata Jaschhof and Hippa (Ecuador).